Outcomes of cerebral venous thrombosis due to vaccine-induced immune thrombotic thrombocytopenia after the acute phase - Munckhof, Anita van de; Lindgren, Erik; Kleinig, Timothy J.; Field, Thalia S.; Cordonnier, Charlotte; Krzywicka, Katarzyna; Poli, Sven; Sánchez van Kammen, Mayte; Borhani-Haghighi, Afshin; Lemmens, Robin; Scutelnic, Adrian; Ciccone, Alfonso; et al. (Stroke, 2022)
Cerebral venous thrombosis (CVT) due to vaccine-induced immune thrombotic thrombocytopenia (VITT) is a severe condition, with high in-hospital mortality rates. Here, we report clinical outcomes of patients with CVT-VITT after SARS-CoV-2 (severe acute respiratory syndrome coronavirus 2) vaccination who survived initial hospitalization.